(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
In this article, the author considered in detail the existing problems connected with the health status, especially the oral health of workers at various industrial enterprises, including residents living in this ecological zone. The author carried out a detailed analysis of scientific research devoted to the study of the mechanisms of the negative impact of industrial waste both on the human body as a whole and on the organs and tissues of the oral cavity, studying their structure, clinic and the formation of pathological processes. Conclusion. Based on the results of the study, negative factors were identified negative factors that arise as a result of the technological production process, which are the main reasons for the appearance and formation of dental diseases, the origin of somatic diseases and a number of complications associated with them, so when providing orthopedic dental care, it is necessary to take into account the importance of the above mentioned factors.